Images of Childhood in Mothers' Accounts of Contemporary Childrearing - Murphy, Elizabeth (Sage, 2007)
This article examines how a sample of first-time mothers in the UK constitute childhood in general, and their own children in particular, in and through their talk about the mundane practices of child-care. The data analysed are drawn from a longitudinal qualitative interview study which followed a sample of mothers from late pregnancy until their babies were two years old. The analysis explores links between mothers’ representations of childhood and the actualities of their child-rearing practices. The extent to which both the representations of childhood and the practices of individual mothers are consistent or contradictory, and change or remain constant over time, is also examined.